Gitanjali:Rabindranath Tagore - Rachanavali - Rabindranath Tagore (Noida Rupa Publications India Pvt. Ltd., 2002)
Gitanjali, or 'Song Offerings'' in English translation, is a volume of 103 poems selected by Tagore from his several Bengali book of poetry. It was largely these poems that took the Western world by storm and brought him worldwide recognition.
Keywords: Poerty; Poerty -- Poetry